1997
DOI: 10.2337/diacare.20.3.314
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Complications and Mortality Among Alaska Natives: 8 Years of Observation

Abstract: We conclude that diabetes is increasing in Alaska Natives, who are experiencing both the microvascular and macrovascular complications of diabetes. The incidence of LEA and ESRD show some evidence of a decrease after intervention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 14 publications
3
46
0
1
Order By: Relevance
“…A decreasing incidence has been reported from many geographic areas where various interventions have been applied (Humphrey et al1996, Schraer et al 1997, Rith-Najarian et al 1998, Calle-Pascual et al 2001, Holstein et al 2001. These studies are usually not populationbased, and have shown a decreasing incidence in a short-term perspective only (Larsson and (Feinglass et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decreasing incidence has been reported from many geographic areas where various interventions have been applied (Humphrey et al1996, Schraer et al 1997, Rith-Najarian et al 1998, Calle-Pascual et al 2001, Holstein et al 2001. These studies are usually not populationbased, and have shown a decreasing incidence in a short-term perspective only (Larsson and (Feinglass et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports from single centers, usually not population-based, have since reported a substantially reduced incidence of major lower extremity amputations in patients with diabetes mellitus following the implementation of various multidisciplinary programs for prevention and treatment of diabetic foot ulcers , Humphrey et al 1996, Schraer et al 1997, Rith-Najarian et al 1998, Calle-Pascual et al 2001, Holstein et al 2001). However, an unchanged or increased incidence of lower-limb amputations has been described by several other authors (Morris et al 1998, Stiegler et al 1998, Pohjolainen and Alaranta 1999, Trautner et al 2001.…”
mentioning
confidence: 99%
“…The 10 year risk of LEA in diabetes varies widely from approximately 1% in Alaskan Natives [44] Barbadians [45] and some UK sites [46]. If lowering blood glucose translates into a lower incidence of LEA, for a population with a 10 year incidence of LEA of 5% [47] and an average HbA 1c of 9.5%, an improvement to an average HbA 1c of 7.5% would reduce the rate of LEA to roughly 3%, all other things being equal.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Within Alaska, the prevalence of metabolic syndrome in two regions was higher than rates for U.S. whites. The rate may currently be low in western Alaska, but given the historical trend toward increasing diabetes and increasing obesity, once might expect the rate to increase in the future.…”
Section: Figmentioning
confidence: 99%